(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This article has built, developed and checked two Solar Air Heaters (SAH). The first absorber layer is constructed of black pine, while the second is made of black aluminum sheet and we have discussed about the Solar Air Heaters and its classification, Function of Solar Air Heater, Application of Solar Air Heater, then wo did experimental setup to analyze the performance of solar air heater which is concluded that the highest efficiency for the SAH at inclination angle was 22 degrees, and the velocity inside the rig. was 1.8 ms. the efficiency of SAH was 94.6 for wood base and 87.4 for sheet metal base.